Longitudinal CT study of parenchymal brain changes in glioma survivors. - Stylopoulos, L A; George, A E; de Leon, M J; Miller, J D; Foo, S H; Hiesiger, E; Wise, A (American Journal of Neuroradiology, 1988)
We reviewed the serial CT studies obtained between 1974 and 1986 of 31 patients with malignant glioma who survived for 2 to 11 years after surgical removal of their tumors. In all cases surgery was followed by radiation therapy to the head (6000 rad) and chemotherapy. Patients were divided into two age groups: those under age 40 (n = 13) and those over age 40 (n = 18). By 2 years all patients in the older group developed evidence of leukoencephalopathy characterized by periventricular zones of decreased attenuation. Only 58% of the younger group showed evidence of white matter changes at this point. All patients from both age groups who survived for 4 years developed leukoencephalopathy. The severity of leukoencephalopathy from 6 months after surgery and beyond was always greater in the older group. All patients developed cerebral atrophy as evidenced by sulcal dilatation and ventricular enlargement. Atrophy was progressive beginning with the first postirradiation scan, and was always more severe in the older patients. A significant difference was found in the clinical status of the two age groups as determined by the mental status score and the Karnofsky scale. Despite progressive brain changes, survivors under age 40 maintained a nearly normal mental status and Karnofsky scores until their death, whereas survivors over age 40 showed progressive clinical decline.